2023
DOI: 10.1186/s11658-023-00449-6
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and erastin emerge synergistic anti-tumor effects on oral squamous cell carcinoma by inducing apoptosis, ferroptosis, and inhibiting autophagy through promoting ROS

Abstract: Background Oral squamous cell carcinomas are one of the most common cancers worldwide with aggressive behavior and poor prognosis. Reactive oxygen species (ROS) are associated with cancer and cause various types of regulated cell death (RCD). Inducing the RCD pathway by modulating ROS levels is imperative to conquer cancers. The aim of this study is to investigate the synergistic anticancer effects of melatonin and erastin on ROS modulation and subsequent RCD induction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…However, HCPT therapy has some adverse clinical effects 36 . It has been reported that HCPT exposure damages mouse oocyte development and quality 37 . In the present study, HCPT exposure caused spermatogenesis damage and poor fecundity in males from juvenile to adult mice.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…However, HCPT therapy has some adverse clinical effects 36 . It has been reported that HCPT exposure damages mouse oocyte development and quality 37 . In the present study, HCPT exposure caused spermatogenesis damage and poor fecundity in males from juvenile to adult mice.…”
Section: Discussionmentioning
confidence: 45%
“…36 It has been reported that HCPT exposure damages mouse oocyte development and quality. 37 In the present study, HCPT exposure caused spermatogenesis damage and poor fecundity in males from juvenile to adult mice. Melatonin is a well-known powerful antioxidant that could promote spermatogonia stem cell proliferation and protect mouse spermatocytes against some medical drugs-induced apoptosis.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Increasingly, studies have been focusing on discovering novel approaches to treat OSCC patients by inducing ferroptosis. For instance, a combinatorial strategy of melatonin and erastin has significant antitumor effects on OSCC cells in vivo by enhancing apoptosis and ferroptosis and suppressing autophagy, 33 providing a new approach to fighting OSCC. In addition, several ferroptosis‐mediated new drug designing systems may be promising in the management of OSCC 34…”
Section: Discussionmentioning
confidence: 99%
“…This has been evaluated both in vitro and in vivo by tampering with the signaling cascades that trigger ferroptosis or silencing of ferroptosis inhibitors, which can be achieved through direct genetic modifications or chemical compounds. Some of the compounds used to achieve such effects are erastin [21,42,57], carnosic acid [34], piperlongumine [58] and Disulfiram [63].…”
Section: Ferroptosismentioning
confidence: 99%